DRIVING FACTORS OF BUSINESS PERFORMANCE: HOW INNOVATION, EXPERIENCE, AND CREATIVITY AFFECT BAMBOO CRAFT ENTERPRISES IN BANYUWANGI - Agustin, Feni Dwi; Fatimah, Feti; Murtaliningtyas, Wenny (Dynamic Management Journal, 2025)
The bamboo craft industry in Banyuwangi Regency holds significant economic potential but faces persistent challenges, including limited innovation, lack of managerial experience, and low entrepreneurial creativity in business strategies. This study addresses the urgent need to enhance the competitiveness of local artisans by empirically examining how innovation, experience, and entrepreneurial creativity influence business success. Using a quantitative associative approach, data were collected via total sampling from bamboo craft entrepreneurs (N=XX) and analyzed through multiple linear regression. The results confirm that all three variables significantly impact business success: innovation increases market relevance, experience improves adaptive management, and entrepreneurial creativity strengthens product and marketing strategies. This study contributes to the literature on creative industries by validating a framework for micro-enterprise development in rural Indonesia. Its novelty lies in integrating these factors within the context of bamboo crafts—a sector often overlooked in entrepreneurial studies—while offering actionable insights for policymakers and business support programs to foster sustainable growth.